Hidden violence is a silent rape: prevention of sexual & gender-based violence against refugees & asylum seekers in Europe: a participatory approach report - Bakker, Hilde (2008)
From the arrival on European territory onwards, young female and male refugees, asylum seekers and undocumented migrants are extremely vulnerable to several types of gender-based violence. This results from the "Hidden Violence is a Silent Rape" Study. This book describes extensively all phases and actions in the project undertaken. We introduce the project, its aims, methods and beneficiaries in Chapter 1 with an overview of the different actions. In Chapter 2 , the results of the Community Based Participatory Research are reported. Chapter 3 and 4 reflect the proceedings and recommendations fo the Hidden Violence is a Silent Rape Seminar